Implementacija smernice ICH M7 in vrednotenje genotoksičnih nečistot - Schmidt, Jan (Farmacevtski vestnik, 2016)
The presence of genotoxic impurities in drug substances and pharmaceutical drug products represents a potential threat for users, especially due to the toxic effects on the genetic material of individuals. Direct genotoxic compounds due to their reactivity, cause DNA damage and are potentially mutagenic. Indirect genotoxic compounds disrupt the DNA integrity through indirect mechanisms not comprising reactions with the DNA. Impurities are regulated by several guidelines of the International Conference on Harmonization (ICH). A new ICH M7 guideline, recently entered into force, precisely defines the assessment and control of genotoxic impurities in pharmaceuticals. The main new feature of this guideline is implementation of two different computational approaches for the prediction of genotoxicity as a main part of decision-making process for classification of genotoxic impurities in order to reduce the number of experimental in vitro studies (e.g. Ames assay). This review represents the new ICH M7 guideline, especially regarding different classes of genotoxic impurities, the approaches to their evaluation, and in silico, in vitro and in vivo methods for the detection of mutagens.
Keywords: (Q)SAR methods; (Q)SAR metode; Ames assay; Amesov test; farmakologija; genotoksične nečistote; genotoxic impurities; ICH M7; mutagenicity; mutagenost